FUNGSI-FUNGSI MANAJEMEN DALAM PENGELOLAAN KURIKULUM - Saajidah, Luthfiyyah (Madrasa: Journal of Islamic Educational Management, 2018)
Madrasa need good curriculum management so that the objectives of implementing Islamic education can be effective and efficient. Curriculum Management is a curriculum management system to provide benefits to users who have been included in the prescribed curriculum. This study aims to uncover management functions including planning, organizing, actuating, and controling the curriculum at MI  Miftahul Huda Bandung, MI At-Taqwa Bandung and MIT PERSIS 24 Bandung. The research method used is a qualitative method. The results of the study show that (1) Curriculum planning St MI Miftahul Huda was carried out through two stages carried out by the madrasa division. While the increase in the curriculum at MI At-Taqwa and MIT PERSIS 24 was only carried out by Madrasas at curriculum development meetings. (2) Organizing using the same curriculum design pattern with curriculum based on subjects (subject curriculum). (3) Actuating of three Madrasas The implementation of learning that began since (4) Controlling was carried out on Students and Educators through supervision 1 or 3 months by the division of education and supervision by Madrasah heads.